Screening for aminoacidopathies using cost effective methods in symptomatic children: A cross sectional study - Fatima, Nazmin; Sonkar, Gyanendra Kumar; Tripathi, Shalini; Singh, Sangeeta; Mahdi, Abbas Ali (Asian Journal of Medical Sciences, 2021)
Background: Inborn errors of metabolism (IEM) are a cluster of hereditary disorders which are caused due to defect in one or more enzymes or disturbance in the protein transport system. Aims and Objective: The aim of this work was to find out the frequency of aminoacidopathies among symptomatic children and to emphasis about cost effective screening of aminoacidopathies in order to minimize morbidity and mortality. Materials and Methods: This cross-sectional study recruited 264 symptomatic children from infants to 15 years of age. Random urine samples (15ml) in sterile container and 1-2 ml of blood in EDTA vials were collected and stored at -20˚C. Color reactions, TLC and HPLC were done in urine and blood samples for amino acid disorders. Results: The prevalence of aminoacidopathies was found high in early age (45.1%), males (55.3%), rural areas (75%) and Muslims (39%). A total of 127 out of 264 (48.1%) symptomatic cases showed at least one of the positive colored tests. Mean hemoglobin level was lower than the normal reference range. 7.7% children had severe anemia (Hb < 7 g/dl). TLC of all these 127 samples was done for amino acids. The results showed positive elevated amino acids in 61 cases (48%). Out of 61 cases only 29 cases were positive for amino acid disorders by HPLC. Generalized aminoaciduria was the common followed by MSUD and tyrosinuria. Based on combination of these three tests, we were able to detect 10.98% (29/264) cases of aminoacidopathies. Conclusions: Hence this study focused using a set of rapid, easy and cost effective simple tests for screening in symptomatic children. There is need to increase the awareness in developing country like India regarding the availability of such affordable and reliable tests.